Divergent Responses of the Diazotrophic Microbiome to Elevated CO2 in Two Rice Cultivars - Yu, Yongjie; Zhang, Jianwei; Petropoulos, Evangelos; Baluja, Marcos Q.; Zhu, Chunwu; Zhu, Jianguo; Lin, Xiangui; Feng, Youzhi (Frontiers in Microbiology, 2018)
The species-specific responses of plant growth to elevated atmospheric CO2 concentration (eCO2) could lead to N limitation and potentially influence the sustainability of ecosystem. Questions remain unanswered with regards to the response of soil N2-fixing community to eCO2 when developing high-yielding agroecosystem to dampen the future rate of increase in CO2 levels and associated climate warming. This study demonstrates the divergent eCO2 influences on the paddy diazotrophic community between weak- and strong-responsive rice cultivars. In response to eCO2, the diazotrophic abundance increased more for the strong-responsive cultivar treatments than for the weak-responsive ones. Only the strong-responsive cultivars decreased the alpha diversity and separated the composition of diazotrophic communities in response to eCO2. The topological indices of the ecological networks further highlighted the different co-occurrence patterns of the diazotrophic microbiome in rice cultivars under eCO2. Strong-responsive cultivars destabilized the diazotrophic community by complicating and centralizing the co-occurrence network as well as by shifting the hub species from Bradyrhizobium to Dechloromonas in response to eCO2. On the contrary, the network pattern of the weak-responsive cultivars was simplified and decentralized in response to eCO2, with the hub species shifting from Halorhodospira under aCO2 to Sideroxydans under eCO2. Collectively, the above information indicates that the strong-responsive cultivars could potentially undermine the belowground ecosystem from the diazotrophs perspective in response to eCO2. This information highlights that more attention should be paid to the stability of the belowground ecosystem when developing agricultural strategies to adapt prospective climatic scenarios by growing high-yielding crop cultivars under eCO2.